A RASCH Analysis of indicators for the evaluation of Integration of Knowledge in the curriculum among academia at the International Islamic University Malaysia - Ismail, Nik Ahmad Hisham; Mamat, Arifin; Muhajir, Muhajir (2013)
A scale of indicators for the Integration of Knowledge (IOK) is developed to evaluate the accomplishment of IOK among academics at International Islamic University Malaysia (IIUM). The function of the study is to identify and validate the dimensions or constructs in the scale that will reflect the IOK at IIUM. From the literature and focus group discussions there are seven notable constructs namely i) academics insights on IOK; ii) IOK in the content of a subject matter, iii) IOK integration in teaching and learning process; iv) IOK in the evaluation of coursework; v) resource person for IOK integration; vi) academic products of IOK; and vii) overall student’s improvement. The study adopted self-constructed instrument. The validation and reliability of the instrument involved pilot study and also panel of experts at the Institute of Education. The study employs a survey to collect data from a purposive sample of academics from different faculties at IIUM. A sample of 306 academics was involved in the study. RASCH analysis was used to calibrate the items as well as providing statistics such as item difficulty, fit statistics and reliability. The findings from RASCH analysis show that i) all items on the scale are the same as the construct being examined; ii) there are sixty five items (65) with fit item that estimates seven variables namely, agreement with the IOK, the practice of IOK in the content, the practice of IOK in the teaching and learning strategies, the practice of IOK in the assessment, the resource person for IOK, the outcome of IOK based on the product, and the emphasis of positive student’s development; iii) there are five items B6-5 (my product of IOK is book),itemB3-17 (in my teaching and learning process, I integrate IOK through games), item B3-13 (in my teaching and learning process, I integrate IOK through patching), item B6-6 (my product of IOK is proceeding), item B4-4 (in the evaluation of my coursework, the IOK is emphasized in Colloquium). While the easiest item is item B1.1 (I believe that IOK is an important mission of IIUM). The study suggests two versions of the scale of indicators of IOK as practiced by academics as to reflect the undergraduate and post graduate programme and curriculum.